1970
DOI: 10.1055/s-0028-1095058
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Diabetogenic Effect of L-Asparaginase by Prednisolone

Abstract: E. ccili L-asparaginase 250 and 500 U/kg given in.a ~ingle I ~V dose did not produce hyperglycemia or g1ycosuna In rabblts. Prednisolone 1 mg/kg/day administered for 14 days was also nondiabetogenic. A combination of L-asparaginase 500 U/Ieg with prednisolone was diabetogenic in all the animals. The results suggest that the two drugs act synergistically in producing the diabetogenic effect The clinical significance oe these fmdings was discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…2; Table 3). Addition of hydrocortisone, however, potentiated the inhibitory effect in analogy with the combined treatment of L-asparaginase and prednisone in man and in rabbits (18). Hydrocortisone was previously shown to influence glucose-induced insulin release and content in a bimodal manner on both mouse (1 9) and rat (20) islets in culture.…”
Section: Resultsmentioning
confidence: 95%
“…2; Table 3). Addition of hydrocortisone, however, potentiated the inhibitory effect in analogy with the combined treatment of L-asparaginase and prednisone in man and in rabbits (18). Hydrocortisone was previously shown to influence glucose-induced insulin release and content in a bimodal manner on both mouse (1 9) and rat (20) islets in culture.…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, two endocrine complications were commonly observed in induction regimen (data not shown), which included a large dose of prednisone. Similarly, the concomitant use of both drugs synergistically increases the occurrence of hyperglycemia and hypertriglyceridemia45.…”
Section: Discussionmentioning
confidence: 99%
“…It has been pos tulated that L-asparaginase inhibits insulin biosynthesis or its secretion from B cells [3,5,6], This effect was also observed in neonatal rat islets in vitro [13,14] and in human pancreatic islets [14].…”
Section: Discussionmentioning
confidence: 82%
“…This enzyme can block protein biosynthesis in several cellular types [2,3]. L-Asparaginase toxicity includes hepatocellular dysfunction, hyper sensitivity, coagulation abnormalities, prerenal azotemic syndrome, central nervous system changes, pancreatitis and a syndrome of hyperglycemia [4], L-Asparaginase can block insulin secretion [5] both in vivo and in vitro, and it has been suggested that L-asparaginase inhibits insulin biosynthesis and/or release [6].…”
Section: Introductionmentioning
confidence: 99%